2012
DOI: 10.1242/jeb.070581
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of metabolism by dietary carbohydrates in two lines of rainbow trout divergently selected for muscle fat content

Abstract: SUMMARYPrevious studies in two rainbow trout lines divergently selected for lean (L) or fat (F) muscle suggested that they differ in their ability to metabolise glucose. In this context, we investigated whether genetic selection for high muscle fat content led to a better capacity to metabolise dietary carbohydrates. Juvenile trout from the two lines were fed diets with or without gelatinised starch (17.1%) for 10weeks, after which blood, liver, muscle and adipose tissues were sampled. Growth rate, feed effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
110
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 73 publications
30
110
8
Order By: Relevance
“…Where both gene expression and enzyme activity have been studied, G6pase expression is often linked to G6Pase enzyme activity (Caseras et al 2002;Méton et al 2004;Saldago et al 2004). However, down regulation of G6Pase gene expression does not automatically mean inhibition of gluconeogenesis, as a recent study performed in trout showed a post-prandial inhibition of G6Pase gene expression was not linked to the modification of G6Pase enzyme activity (Skiba-Cassy et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Where both gene expression and enzyme activity have been studied, G6pase expression is often linked to G6Pase enzyme activity (Caseras et al 2002;Méton et al 2004;Saldago et al 2004). However, down regulation of G6Pase gene expression does not automatically mean inhibition of gluconeogenesis, as a recent study performed in trout showed a post-prandial inhibition of G6Pase gene expression was not linked to the modification of G6Pase enzyme activity (Skiba-Cassy et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Anti-phospho Akt (Ser473), anti-carboxyl terminal Akt, anti-phospho AMPK (Thr172), anti-AMPK, anti-phospho-FoxO1 (Thr24) and antiFoxO1 (L27) antibodies were used (Cell Signaling Technology, Saint Quentin Yvelings, France). All these antibodies cross-react successfully with rainbow trout proteins of interest (Skiba-Cassy et al, 2009;Kamalam et al, 2012;Velasco et al, 2016b). After washing, membranes were incubated with an IgG-HRP secondary antibody (Bio-Rad) and spots were quantified by Image Lab software version 5.2.1 (Bio-Rad).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The primer sequences used in the real-time RT-PCR assays as well as the protocol conditions of the assays for mRNA of glucose and amino acid metabolic genes (Kamalam et al, 2012;Kamalam et al, 2013) and miRNAs (Mennigen et al, 2012) have previously been published. The transcripts analysed were glucokinase (GK; EC 2.7.1.2), hexokinase 1 (HK1; EC 2.7.1.1), 6-phosphofructo-1-kinase (6PFK; EC 2.7.1.11) and pyruvate kinase (Dumortier et al, 2013;Ramírez et al, 2013).…”
Section: Relative Quantification Of Mrna and Mirnamentioning
confidence: 99%
“…An amount of 1 μg of total RNA was used for cDNA synthesis. The NCode TM VILO TM miRNA cDNA Synthesis Kit (Invitrogen) or the SuperScript III RNaseH-Reverse Transcriptase Kit (Invitrogen) with random primers (Promega, Charbonniéres, France) was used according to the manufacturer's protocol to synthesize cDNA (n=9 for each time point) for miRNA and mRNA, respectively.The primer sequences used in the real-time RT-PCR assays as well as the protocol conditions of the assays for mRNA of glucose and amino acid metabolic genes (Kamalam et al, 2012;Kamalam et al, 2013) and miRNAs (Mennigen et al, 2012) have previously been published. The transcripts analysed were glucokinase (GK; EC 2.7.1.2), hexokinase 1 (HK1; EC 2.7.1.1), 6-phosphofructo-1-kinase (6PFK; EC 2.7.1.11) and pyruvate kinase (Dumortier et al, 2013;Ramírez et al, 2013).…”
mentioning
confidence: 99%